THE INFLUENCE OF HEALTH EDUCATION WITH AUDIO VISUAL MEDIA ON CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) IN GRADE III-V STUDENTS AT WANUROJO KEMIRI PURWOREJO STATE ELEMENTARY SCHOOL - Eka Kurnia Astuti (Jurnal EduHealth, 2020)
Clean and Healthy Living Behaviors (PHBS) in children are very important so that good health education is needed. Health education with audio visual media will improve clean and healthy living behaviors because children can hear and see firsthand clean and healthy living behaviors that are good and correct.It is known the influence of health education with audio visual media on clean and healthy living behavior (PHBS) in grade III-V students at Wanurojo Kemiri Purworejo State Elementary School. The design of this study uses pre experiment (one group pretest posttest). Respondents in this study numbered 45 students aged 8-11 years. The study was conducted on February 25 -28, 2014.Health education with audio visual media affects clean and healthy living behavior (PHBS) in grade III-V students at Wanurojo Kemiri Purworejo State Elementary School (P<0.01). Because health education with audio visual media is influential in improving clean and healthy living behaviors, health education with audio visual media can be utilized to improve clean and healthy living behaviors of elementary school children.